Near-infrared light absorbing glass, element and light filter
By rationally designing the cationic and anionic components of the near-infrared light absorbing glass, the problem of insufficient transmittance in the visible light region or insufficient absorption performance in the near-infrared light absorbing glass in the prior art is solved, and excellent visible light transmission characteristics and near-infrared light absorption characteristics are achieved, meeting the miniaturization needs of optical equipment.
Patent Information
- Application Number
- CN202411889460.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the near-infrared light absorbing glass has insufficient transmittance in the visible light region or insufficient absorption performance in the near-infrared region, which cannot meet the miniaturization needs of optical equipment.
By rationally designing the cationic and anionic components, the specific content range is: P5+: 38-52%, Al3+: 3-12%, Cu2+: 2-16%, Rn+: 10-35%, R2+: 3-35%, O2-: 82-97%, F-: 3-18%, to achieve excellent visible light transmission characteristics and near-infrared light absorption characteristics.
It has achieved excellent transmission characteristics in the visible light region and excellent absorption characteristics in the near infrared region, which meets the miniaturization needs of optical equipment.
Smart Images

Figure BDA0005200269560000141 
Figure BDA0005200269560000161 
Figure BDA0005200269560000171
Abstract
Description
Technical Field
[0001] The invention relates to glass, in particular to near-infrared light absorbing glass, and a near-infrared light absorbing element and an optical filter made of the glass. Background Art
[0002] In recent years, the spectral sensitivity of semiconductor imaging elements such as CCD and CMOS used in digital cameras, camera phones and VTR cameras has spread from the visible field to the near-infrared field. Using filters that absorb light in the near-infrared field can obtain a visual sensitivity close to that of humans. The wavelength of visible light that the average human eye can perceive is between 400 and 700nm. Therefore, by using filters that absorb near-infrared light, images with brightness factors close to those of the human eye can be obtained. With the miniaturization of optical modules and the increase in reliability requirements, higher requirements are placed on the near-infrared light absorbing glass used to manufacture such filters. Such glass is required to have excellent transmission characteristics in the visible field and excellent absorption characteristics in the near-infrared region.
[0003] In the prior art, Cu is generally added to phosphate system or fluorophosphate system glass. 2+ To manufacture near-infrared light absorbing glass. For example, Chinese patent CN104341105A discloses a near-infrared light absorbing glass, which has insufficient absorption performance in the near-infrared region and needs to increase the thickness of the glass to meet the requirements of spectral performance, but cannot meet the miniaturization requirements of optical equipment, or has insufficient transmittance in the visible light region, affecting the filtering performance. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a near-infrared light absorbing glass having excellent transmittance in the visible light region and excellent absorption performance in the near-infrared region.
[0005] The technical solution adopted by the present invention to solve the technical problem is:
[0006] (1) Near-infrared light absorbing glass, the components of which are expressed in molar percentages, the cationic component containing: P 5+ :38~52%;Al 3+ :3~12%;Cu 2+ :2~16%;Rn + :10~35%; R 2+ : 3-35%, said Rn + For Li + 、Na + , K + One or more of R 2+ Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+One or more of;
[0007] The anion component contains: O 2- :82~97%;F - :3~18%.
[0008] (2) The near-infrared light absorbing glass according to (1), wherein the components are expressed in molar percentages, and the cationic component further comprises: Ln 3+ :0~8%;and / or B 3+ :0~5%;and / or Si 4+ :0~5%;and / or Zn 2+ :0~10%;and / or Sb 3+ : 0~3%, said Ln 3+ For La 3+ , Gd 3+ , Y 3+ One or more of;
[0009] The anion component also contains: Cl - +Br - +I - :0~2%.
[0010] (3) Near-infrared light absorbing glass, the components of which are expressed in molar percentages, the cationic components are P 5+ :38~52%;Al 3+ :3~12%;Cu 2+ :2~16%;Rn + :10~35%; R 2+ :3~35%;Ln 3+ :0~8%; B 3+ :0~5%;Si 4+ :0~5%; Zn 2+ :0~10%; Sb 3+ : 0 to 3%, the Rn + For Li + 、Na + , K + One or more of R 2+ Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ One or more of Ln 3+ For La 3+ , Gd 3+ , Y 3+ One or more of;
[0011] The anion component is O 2- :82~97%;F -:3~18%;Cl - +Br - +I - : 0~2% composition.
[0012] (4) Near-infrared light absorbing glass, whose cation component contains P 5+ 、Al 3+ , Cu 2+ , Rn + and R 2+ , the Rn + For Li + 、Na + , K + One or more of R 2+ Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ One or more of the anion components contain O 2- and F - , near-infrared light absorbing glass with a thickness of less than 0.4 mm, spectral transmittance τ at a wavelength of 400 nm 400 80.0% or more, 500nm wavelength spectral transmittance τ 500 The spectral transmittance at 1100nm is 83.0% or more. 1100 It is less than 20.0%.
[0013] (5) Near-infrared light absorbing glass, whose cation component contains P 5+ 、Al 3+ , Cu 2+ , Rn + and R 2+ , the Rn + For Li + 、Na + , K + One or more of R 2+ Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ One or more of the anion components contain O 2- and F - , for near-infrared light absorbing glass with a thickness of less than 0.4 mm, the wavelength λ corresponding to the spectral transmittance within the wavelength range of 500 to 700 nm when the transmittance reaches 50% 50 Below 640nm.
[0014] (6) Near-infrared light absorbing glass, the cation component of which contains P 5+ 、Al 3+ , Cu 2+ , Rn+ and R 2+ , where the Rn + is one or more of Li + , Na + , K + , and R 2+ is one or more of Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ , and the anion component contains O 2- and F - , and the acid resistance stability D of the near-infrared light absorbing glass A is above Class 3.
[0015] (7) For the near-infrared light absorbing glass according to any one of (4) to (6), the cation component contains: P 5+ : 40 - 54%; and / or Al 3+ : 3 - 12%; and / or Cu 2+ : 2 - 16%; and / or Rn + : 3 - 25%; and / or R 2+ : 5 - 35%; and / or Ln 3+ : 0 - 8%; and / or B 3+ : 0 - 5%; and / or Si 4+ : 0 - 5%; and / or Zn 2+ : 0 - 10%; and / or Sb 3+ : 0 - 3%, where the Rn + is one or more of Li + , Na + , K + , and R 2+ is one or more of Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ , and Ln 3+ is one or more of La 3+ , Gd 3 + , Y 3+ .
[0016] (8) For the near-infrared light absorbing glass according to any one of (4) to (7), the anion component contains: O 2- : 70 - 97%; and / or F - : 3 - 30%; and / or Cl - +Br - +I - : 0 - 2%.
[0017] (9) The near-infrared light absorbing glass according to any one of (1) to (8), wherein the components are expressed in molar percentages, wherein: Rn + / (52%-P 5+ ) is 1.0 to 25.0, preferably Rn + / (52%-P 5+ ) is 1.4 to 20.0, and more preferably Rn + / (52%-P 5+ ) is 1.8 to 15.0, and more preferably Rn + / (52%-P 5+ ) is 2.2 to 10.0, and more preferably Rn + / (52%-P 5+ ) is 2.4 to 7.0, and the Rn + For Li + 、Na + , K + One or more of .
[0018] (10) The near-infrared light absorbing glass according to any one of (1) to (9), wherein the components are expressed in molar percentages, wherein: Al 3+ / Mg 2+ 1.0~10.0, preferably Al 3+ / Mg 2+ 1.1 to 8.0, more preferably Al 3+ / Mg 2+ 1.2 to 6.0, more preferably Al 3+ / Mg 2+ 1.3 to 4.0, more preferably Al 3+ / Mg 2+ It is 1.5 to 2.5.
[0019] (11) The near-infrared light absorbing glass according to any one of (1) to (10), wherein the components are expressed in molar percentages, wherein: Mg 2+ / Cu 2+ 0.1~1.8, preferably Mg 2+ / Cu 2+ 0.1 to 1.6, more preferably Mg 2+ / Cu 2+ 0.2 to 1.4, more preferably Mg 2+ / Cu 2+ 0.3 to 1.2, more preferably Mg 2+ / Cu 2+ It is 0.4~1.0.
[0020] (12) The near-infrared light absorbing glass according to any one of (1) to (11), wherein the components are expressed in molar percentages, wherein: Rn+ / Mg 2+ 2.0 to 30.0, preferably Rn + / Mg 2+ Rn is 2.5 to 24.0, and more preferably + / Mg 2+ is 3.0 to 18.0, and more preferably Rn + / Mg 2+ 3.5 to 12.0, and more preferably Rn + / Mg 2+ is 4.0 to 9.0, and the Rn + For Li + 、Na + , K + One or more of .
[0021] (13) The near-infrared light absorbing glass according to any one of (1) to (12), wherein the components are expressed in molar percentages, wherein: R 2+ / Mg 2+ 2.0~20.0, preferably R 2+ / Mg 2+ 2.2 to 15.0, more preferably R 2+ / Mg 2+ is 2.3 to 10.0, and more preferably R 2+ / Mg 2+ is 2.4 to 7.0, and more preferably R 2+ / Mg 2+ is 2.5 to 6.0, the R 2+ Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ One or more of .
[0022] (14) The near-infrared light absorbing glass according to any one of (1) to (13), wherein the components are expressed in molar percentages, wherein: Ba 2+ / Cu 2+ 0.2 to 3.0, preferably Ba 2+ / Cu 2+ 0.3 to 2.5, more preferably Ba 2+ / Cu 2+ is 0.4 to 2.0, and Ba is more preferably 2+ / Cu 2+ is 0.5 to 1.5, and Ba is more preferably 2+ / Cu 2+ It is 0.5~1.0.
[0023] (15) The near-infrared light absorbing glass according to any one of (1) to (14), wherein the composition is expressed in molar percentage, wherein: Zn 2+ / Cu 2+ 0 to 1.2, preferably Zn 2+ / Cu 2+ 0 to 1.1, more preferably Zn 2+ / Cu 2+ is 0 to 0.9, and Zn is more preferred 2+ / Cu 2+ 0 to 0.7, and more preferably Zn 2+ / Cu 2+ It is 0 to 0.5.
[0024] (16) The near-infrared light absorbing glass according to any one of (1) to (15), wherein the components are expressed in molar percentages, wherein: - / Mg 2+ 0.5~15.0, preferably F - / Mg 2+ 0.8 to 10.0, more preferably F - / Mg 2+ is 1.1 to 8.0, and more preferably F - / Mg 2+ is 1.3 to 6.0, and more preferably F - / Mg 2+ It is 1.5 to 4.0.
[0025] (17) The near-infrared light absorbing glass according to any one of (1) to (16), wherein the components are expressed in molar percentages, wherein: (0.3×P 5+ +F - ) / Cu 2+ 1.5 to 9.0, preferably (0.3×P 5+ +F - ) / Cu 2+ 2.4 to 7.5, more preferably (0.3 × P 5+ +F - ) / Cu 2+ 3.3 to 6.0, more preferably (0.3×P 5+ +F - ) / Cu 2+ It is 3.5 to 5.5.
[0026] (18) The near-infrared light absorbing glass according to any one of (1) to (17), wherein the components are expressed in molar percentages, wherein: 5+ : 42~51%, preferably P 5+ : 44-50%; and / or Al 3+ : 4-10%, preferably Al3+ : 5-8%; and / or Cu 2+ : 3-10%, preferably Cu 2+ : 4-8%; and / or Rn + : 15-30%, preferably Rn + : 20-28%; and / or R 2+ : 5-30%, preferably R 2 + :10~20%;and / or Ln 3+ : 0~6%, preferably Ln 3+ : 0 to 4%, preferably no Ln 3+ ; and / or B 3+ : 0-2%, preferably B 3+ : 0 to 1%, preferably no B 3+ ; and / or Si 4+ : 0-2%, preferably Si 4+ : 0 to 1%, preferably no Si 4+ ; and / or Zn 2+ : 0-6%, preferably Zn 2+ : 0 to 4%, preferably no Zn 2+ ; and / or Sb 3+ : 0-2%, preferably Sb 3+ :0.01~1%, said Rn + For Li + 、Na + , K + One or more of R 2+ Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ One or more of Ln 3 + For La 3+ , Gd 3+ , Y 3+ One or more of .
[0027] (19) The near-infrared light absorbing glass according to any one of (1) to (18), wherein the components are expressed in molar percentages, wherein: Li + : 0-10%, preferably Li + : 0-7%, more preferably Li + :0~5%;and / or Na + : 10-32%, preferably Na + : 15-30%, more preferably Na + :20~28%;and / or K + : 0~10%, preferably K +: 0 to 7%, more preferably K + : 0 to 5%; and / or Mg 2 + : 1 to 10%, preferably Mg 2+ : 2 to 7%, more preferably Mg 2+ : 3 to 6%; and / or Ca 2+ : 1 to 10%, preferably Ca 2+ : 2 to 7%, more preferably Ca 2+ : 3 to 6%; and / or Sr 2+ : 0 to 10%, preferably Sr 2+ : 1 to 8%, more preferably Sr 2+ : 2 to 6%; and / or Ba 2+ : 1 to 10%, preferably Ba 2+ : 2 to 8%, more preferably Ba 2+ : 3 to 6%; and / or Y 3+ : 0 to 6%, preferably Y 3+ : 0 to 5%, more preferably Y 3 + : 0 to 2%; and / or La 3+ : 0 to 5%, preferably La 3+ : 0 to 3%, more preferably La 3+ : 0 to 1%; and / or Gd 3+ : 0 to 5%, preferably Gd 3+ : 0 to 3%, more preferably Gd 3+ : 0 to 1%.
[0028] (20) The near-infrared light-absorbing glass according to any one of (1) to (19), wherein the components are expressed in mole percentages, where: O 2- : 85 to 95%, preferably: O 2- : 87 to 93%; and / or F - : 5 to 15%, preferably F - : 7 to 13%; and / or Cl - +Br - +I - : 0 to 1%, preferably Cl - +Br - +I - : 0 to 0.5%.
[0029] (21) The water resistance stability D of the near-infrared light-absorbing glass according to any one of (1) to (20) W is Class 1; and / or the acid resistance stability D A is Class 3 or above, preferably Class 2 or above; and / or the transformation temperature T g380 to 460°C, preferably 385 to 450°C, more preferably 390 to 440°C, and further preferably 395 to 430°C; and / or density ρ is 3.5 g / cm 3 Below, preferably 3.4 g / cm 3 Below, more preferably 3.3 g / cm 3 Below, more preferably 3.2 g / cm 3 Below; and / or hardness H k 300kgf / mm 2 Above, preferably 310kgf / mm 2 More preferably 320kgf / mm 2 More preferably, 330 kgf / mm 2 and / or Young's modulus E is 5500×10 7 ~7500×10 7 Pa, preferably 5700×10 7 ~7000×10 7 Pa, more preferably 5900×10 7 ~6900×10 7 Pa.
[0030] (22) The near-infrared light absorbing glass according to any one of (1) to (21), wherein the near-infrared light absorbing glass has a thickness of 0.4 mm or less and a spectral transmittance τ at a wavelength of 400 nm. 400 80.0% or more, preferably 82.0% or more, more preferably 84.0% or more; and / or the spectral transmittance τ at a wavelength of 500 nm 500 83.0% or more, preferably 85.0% or more, more preferably 88.0% or more; and / or the spectral transmittance τ at a wavelength of 1100 nm 1100 20.0% or less, preferably 18.0% or less, more preferably 16.0% or less, and further preferably 14.0% or less; and / or the wavelength λ corresponding to the spectral transmittance at 50% in the wavelength range of 500 to 700 nm. 50 The wavelength is 640 nm or less, preferably 610 to 635 nm, and more preferably 615 to 630 nm.
[0031] (23) The near-infrared light absorbing glass according to (22), wherein the thickness of the near-infrared light absorbing glass is 0.05 to 0.4 mm, preferably 0.1 to 0.3 mm, more preferably 0.15 to 0.25 mm, and further preferably 0.15 mm, 0.18 mm, 0.20 mm, 0.21 mm, 0.23 mm, or 0.25 mm.
[0032] (24) A near-infrared light absorbing glass element, which is made of the near-infrared light absorbing glass described in any one of (1) to (23).
[0033] (25) An optical filter comprising the near-infrared light absorbing glass described in any one of (1) to (23), or a near-infrared light absorbing glass element described in (24).
[0034] (26) A device comprising the near-infrared light absorbing glass described in any one of (1) to (23), or the near-infrared light absorbing glass element described in (24), or the optical filter described in (25).
[0035] The beneficial effects of the present invention are as follows: through reasonable component design, the near-infrared light absorbing glass obtained by the present invention has excellent transmission characteristics in the visible light region and excellent absorption characteristics in the near-infrared region. DETAILED DESCRIPTION
[0036] The embodiments of the near-infrared light absorbing glass of the present invention are described in detail below, but the present invention is not limited to the embodiments described below, and can be implemented with appropriate changes within the scope of the purpose of the present invention. In addition, although the description of the repeated description may be appropriately omitted, the gist of the invention is not limited thereto. In the following description, the near-infrared light absorbing glass of the present invention is sometimes referred to as glass.
[0037] [Near-infrared light absorbing glass]
[0038] The following is an explanation of the scope of each component (ingredient) of the near-infrared light absorbing glass of the present invention. In this specification, unless otherwise specified, the content of the cationic component is expressed as the molar percentage (mol%) of the cation in all cationic components, and the content of the anionic component is expressed as the molar percentage of the anion in all anionic components; the ratio between the contents of the cationic components is the ratio of the molar percentage contents between the contents of the cationic components; the ratio between the contents of the anionic components is the ratio of the molar percentage contents between the contents of the anionic components; the total content is expressed in ion molar percentages; the ratio between the contents of the anionic and cation components is the ratio between the molar percentage contents of the cationic component in all cationic components and the molar percentage contents of the anionic component in all anionic components. In the description of the relationship between the contents of the components in the present invention, if it involves a multiplication and / or division relationship, the component content is calculated using the actual numerical value corresponding to its percentage. For example, when the component content percentage is 10%, it is calculated as 0.1 in the multiplication and / or division relationship.
[0039] Unless otherwise indicated in specific circumstances, the numerical ranges listed herein include upper and lower limits, "above" and "below" include endpoint values, and all integers or fractions included in the range, without being limited to the specific values listed when the range is defined. "And / or" referred to herein is inclusive, for example, "A and / or B" means only A, or only B, or both A and B.
[0040] It should be noted that the ionic valences of the components described below are representative values used for convenience and are not different from other ionic valences. The ionic valences of the components in the glass may be other than the representative values. For example, P usually exists in the glass in a state of +5 ionic valence, so in this patent, "P 5+ " is used as a representative value, but there is the possibility of existing in other ionic valence states, which is also within the scope of protection of this patent.
[0041] <Cationic component>
[0042] P 5+ It is an indispensable component of the glass skeleton of the present invention, which can promote the formation of glass and help improve the near-infrared absorption performance of glass. 5+ If the content of P is lower than 38%, the above effect is not sufficient and the near-infrared absorption function of the glass is difficult to meet the design requirements; 5+ When the content of P exceeds 52%, the chemical stability and weather resistance of the glass decrease rapidly. 5+ The content is 38 to 52%, preferably 42 to 51%, and more preferably 44 to 50%.
[0043] Al 3+ It is beneficial to increase the stability of glass, improve the strength of glass and improve the weather resistance of glass. However, if its content exceeds 12%, the crystallization tendency of glass increases and the melting performance of glass deteriorates. 3+ The content is 3 to 12%, preferably 4 to 10%, and more preferably 5 to 8%.
[0044] Cu 2+ It is a necessary component for the glass of the present invention to obtain near-infrared light absorption performance. If its content is less than 2%, the near-infrared absorption performance of the glass is difficult to meet the design requirements. However, if Cu 2+ When the content of Cu exceeds 16%, the transmittance of the glass in the visible light region decreases, the valence state of Cu in the glass changes, it is difficult to obtain the desired near-infrared light absorption performance, and the devitrification resistance of the glass decreases. 2+ The content of is 2 to 16%, preferably 3 to 10%, and more preferably 4 to 8%.
[0045] R + (Rn +For Li + 、Na + , K + One or more of these) can reduce the melting temperature and viscosity of the glass and promote the 2+ The state exists, but with Rn + The chemical stability of the glass deteriorates and the anti-crystallization performance also deteriorates rapidly. + To obtain the above effect, but when Rn + When the content of Rn exceeds 35%, the devitrification resistance of the glass decreases, the forming performance of the glass deteriorates, and the hardness decreases. + The content of is 10 to 35%, preferably 15 to 30%, and more preferably 20 to 28%.
[0046] The inventors have found through a large number of experimental studies that in some embodiments, controlling Rn + / (52%-P 5+ ) is within the range of 1.0 to 25.0, the glass can obtain excellent chemical stability and a higher visible light transmittance. + / (52%-P 5+ ) is 1.0 to 25.0, and more preferably Rn + / (52%-P 5+ ) is 1.4 to 20.0, and more preferably Rn + / (52%-P 5+ ) is 1.8 to 15.0, and more preferably Rn + / (52%-P 5+ ) is 2.2 to 10.0, and further preferably Rn + / (52%-P 5+ ) is 2.4~7.0.
[0047] Li + It is a component that improves the melting property of glass. However, when Li + When the content exceeds 10%, the devitrification resistance, forming performance and hardness of the glass decrease, and the glass cost increases. + The content is 0 to 10%, preferably 0 to 7%, and more preferably 0 to 5%.
[0048] Na + Compared with Li + It can significantly reduce the melting temperature and viscosity of glass, and improve the "alkalinity" of glass, making the Cu in glass 2+ It exists in the form of Na, which improves the visible light transmittance of the glass and achieves a better effect of filtering near-infrared light. However, too much Na +This will make the glass difficult to shape and reduce the hardness of the glass. + The content of is 10 to 32%, preferably 15 to 30%, and more preferably 20 to 28%.
[0049] K + Has strong fluxing and maintenance of Cu 2+ However, when its content exceeds 10%, the chemical stability and devitrification resistance of the glass will be greatly reduced. + The content is 0 to 10%, preferably 0 to 7%, and more preferably 0 to 5%.
[0050] R 2+ (R 2+ Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ One or more of the above) can be used to reduce the melting temperature of glass and improve the glass forming stability and hardness. 2+ If the content of R exceeds 35%, the devitrification resistance of the glass decreases. 2+ The content of is 3 to 35%, preferably 5 to 30%, more preferably 10 to 20%.
[0051] Mg 2+ It can enhance the chemical stability of glass and improve the processing performance of glass. If its content exceeds 10%, the anti-crystallization performance of glass will decrease and the visible light transmittance will decrease. 2+ The content of Mg is 1-10%, preferably Mg 2+ The content of Mg is 2-7%, more preferably Mg 2+ The content is 3-6%.
[0052] In some embodiments, Al 3+ The content of Mg 2+ The ratio between the content of Al 3+ / Mg 2+ When the value is controlled within the range of 1.0 to 10.0, the glass can obtain good thermal stability and suitable Young's modulus. 3+ / Mg 2+ 1.0 to 10.0, more preferably Al 3+ / Mg 2+ is 1.1 to 8.0, and Al is more preferred 3+ / Mg 2+ 1.2 to 6.0, more preferably Al 3+ / Mg 2+ 1.3 to 4.0, and Al 3+ / Mg 2+It is 1.5 to 2.5.
[0053] In some embodiments, Mg 2+ The content of Cu 2+ The ratio between the content of Mg 2+ / Cu 2+ If the Mg is controlled below 1.8, the glass can easily obtain excellent visible light transmittance; 2+ / Cu 2+ If the glass is too low, the Young's modulus of the glass will decrease. 2+ / Cu 2+ 0.1 to 1.8, more preferably Mg 2+ / Cu 2+ 0.1 to 1.6, more preferably Mg 2+ / Cu 2+ 0.2 to 1.4, more preferably Mg 2+ / Cu 2+ 0.3 to 1.2, and Mg is further preferred 2+ / Cu 2+ It is 0.4~1.0.
[0054] The inventors have found through a large number of experimental studies that controlling Rn + / Mg 2+ In the range of 2.0 to 30.0, the glass can maintain good chemical stability while preventing the glass transition temperature from rising. + / Mg 2+ 2.0 to 30.0, more preferably Rn + / Mg 2+ is 2.5 to 24.0, and more preferably Rn + / Mg 2+ 3.0 to 18.0, and more preferably Rn + / Mg 2+ is 3.5 to 12.0, and further preferably Rn + / Mg 2+ It is 4.0~9.0.
[0055] In some embodiments, R 2+ The content of Mg 2+ The ratio R between the contents 2+ / Mg 2+ If R is controlled within the range of 2.0 to 20.0, the anti-crystallization performance of the glass can be improved and a suitable Young's modulus can be obtained. 2+ / Mg 2+ If the value is lower than 2.0, the visible light transmittance of the glass will decrease. 2+ / Mg 2+2.0 to 20.0, more preferably R 2+ / Mg 2+ is 2.2 to 15.0, and more preferably R 2+ / Mg 2+ is 2.3 to 10.0, and more preferably R 2+ / Mg 2+ is 2.4 to 7.0, and R 2 + / Mg 2+ It is 2.5 to 6.0.
[0056] By containing more than 1% of Ca 2+ It can enhance the anti-crystallization performance of glass and improve the Young's modulus of glass, but when its content exceeds 10%, the "alkalinity" of glass is insufficient, resulting in poor spectral performance. 2+ The content is 1 to 10%, preferably 2 to 7%, and more preferably 3 to 6%.
[0057] Sr 2+ It can improve the chemical stability of glass and increase visible light transmittance, but if its content exceeds 10%, the anti-crystallization performance of glass will decrease. 2+ The content of is 0 to 10%, preferably 1 to 8%, and more preferably 2 to 6%.
[0058] Ba 2+ It can improve the transmittance of glass in the visible light region, improve the chemical stability of glass, and enhance the strength of glass. In the present invention, by containing more than 1% Ba 2+ To obtain the above effect, but if Ba 2+ If the content of Ba exceeds 10%, the density of the glass increases and the anti-crystallization performance deteriorates. 2+ The content of Ba is 1-10%, preferably Ba 2+ The content of Ba is 2 to 8%, and Ba is more preferred. 2+ The content is 3-6%.
[0059] In some embodiments, controlling Ba 2+ The content of Cu 2+ The ratio between the contents of 2+ / Cu 2+ In the range of 0.2 to 3.0, the thermal stability and visible light transmittance of the glass can be improved while preventing the density of the glass from increasing. 2+ / Cu 2+ 0.2 to 3.0, more preferably Ba 2+ / Cu 2+ is 0.3 to 2.5, and Ba is more preferably 2+ / Cu 2+is 0.4 to 2.0, and Ba is more preferably 2+ / Cu 2+ is 0.5 to 1.5, and Ba is further preferred 2+ / Cu 2+ It is 0.5~1.0.
[0060] Ln 3+ (Ln 3+ For La 3+ , Gd 3+ , Y 3+ One or more of the above) is beneficial to improving the visible light transmittance and near infrared absorption performance of the glass, and improving the chemical stability and hardness of the glass. If its content exceeds 8%, the anti-crystallization performance of the glass will deteriorate. 3+ The content of Ln is 0 to 8%, preferably 0 to 6%, and more preferably 0 to 4%. 3+ .Y 3+ Compared with La in glass 3+ and Gd 3+ , which is more conducive to obtaining the desired spectral characteristics of the present invention, therefore, it is preferred that Y 3+ The content of Y is 0-6%, more preferably 3+ The content of Y is 0 to 5%, and Y 3+ The content is 0-2%; preferably La 3+ The content of La is 0-5%, and La 3+ The content of La is 0 to 3%, and La is more preferred. 3+ The content is 0-1%; preferably Gd 3+ The content of Gd is 0-5%, and more preferably 3+ The content of Gd is 0 to 3%, and more preferably 3+ The content is 0-1%.
[0061] B 3+ It can reduce the melting temperature of glass. When its content exceeds 5%, the near-infrared light absorption characteristics of glass decrease. 3+ The content is 0 to 5%, preferably 0 to 2%, and more preferably 0 to 1%. In some embodiments, it is further preferred that B is not contained. 3+ .
[0062] Si 4+ It can promote the formation of glass and improve the chemical stability of glass. If its content exceeds 5%, the melting property of glass will be deteriorated, unmelted impurities will be easily formed in the glass, and the near-infrared light absorption characteristics of glass will be easily reduced. 4+ The content of Si is 0 to 5%, preferably 0 to 2%, and more preferably 0 to 1%. In some embodiments, it is further preferred that Si is not contained.4+ .
[0063] Zn 2+ In Cu 2+ When the content is high, the thermal stability of the glass can be greatly improved. 2+ When the content of Zn exceeds 10%, the visible light transmittance decreases. 2+ The content of Zn is 0 to 10%, preferably 0 to 6%, and more preferably 0 to 4%. In some embodiments, it is further preferred that Zn is not contained. 2+ .
[0064] The inventors have found through a large number of experimental studies that in some embodiments, an appropriate amount of Zn 2+ It helps to improve the anti-crystallization performance of the glass. However, in the present invention, if Zn 2+ / Cu 2+ A ratio higher than 1.2 will result in poor spectral properties and reduced hardness of the glass. 2+ / Cu 2+ 0 to 1.2, more preferably Zn 2+ / Cu 2+ is 0 to 1.1, and Zn is more preferred 2+ / Cu 2+ is 0 to 0.9, and Zn is more preferred 2+ / Cu 2+ is 0 to 0.7, and Zn is further preferred 2+ / Cu 2+ It is 0 to 0.5.
[0065] Sb 3+ It is the clarifier of the present invention. By containing a small amount of clarifier components, the clarification effect of the glass can be improved, bubbles inside the glass can be eliminated, and an excellent bubble degree grade can be obtained. At the same time, an oxidizing atmosphere can be provided for the glass, so that Cu is Cu 2+ The Sb in the present invention exists in the form of 3+ The content is 0 to 3%, preferably 0 to 2%, and more preferably 0.01 to 1%.
[0066] <Anion component>
[0067] O 2- It is an important anion component in the glass of the present invention, which can stabilize the glass network structure, form stable glass, and ensure that the Cu in the glass is Cu 2+ The glass exists in the form of, thus ensuring the glass's ability to absorb light in the near-infrared region. 2- If the content of Cu is too small, it is difficult to form stable glass, and Cu 2+ Easily reduced to Cu +, but it cannot achieve the effect of absorbing light in the near-infrared region; 2- When the content of O is too high, the melting temperature of the glass will be higher, resulting in a significant decrease in the spectral transmittance in the visible light domain. 2- The content is 82 to 97%, preferably 85 to 95%, and more preferably 87 to 93%.
[0068] F - It can reduce the melting temperature of glass, increase the transmittance of glass in the visible light region, reduce the viscosity of glass, and contain an appropriate amount of F - It is beneficial to improve the anti-crystallization performance of glass. - When the content exceeds 18%, the stability of the glass decreases, the glass is easily volatile during melting, causing environmental pollution, and the glass is prone to form streaks. - The content is 3 to 18%, preferably 5 to 15%, and more preferably 7 to 13%.
[0069] In some embodiments, controlling F - The content of Mg 2+ The ratio between the contents of - / Mg 2+ In the range of 0.5 to 15.0, the glass can obtain a suitable Young's modulus and good anti-crystallization performance. - / Mg 2+ 0.5 to 15.0, more preferably F - / Mg 2+ is 0.8 to 10.0, and more preferably F - / Mg 2+ is 1.1 to 8.0, and more preferably F - / Mg 2+ 1.3 to 6.0, and further preferably F - / Mg 2+ It is 1.5 to 4.0.
[0070] In some embodiments, by controlling (0.3×P 5+ +F - ) / Cu 2+ In the range of 1.5 to 9.0, the near-infrared absorption performance of the glass can be improved while obtaining good anti-crystallization performance. 5+ +F - ) / Cu 2+ 1.5 to 9.0, more preferably (0.3 × P 5+ +F - ) / Cu 2+ 2.4 to 7.5, more preferably (0.3 × P 5+ +F - ) / Cu2+ 3.3 to 6.0, more preferably (0.3×P 5+ +F - ) / Cu 2+ It is 3.5 to 5.5.
[0071] Cl - Br - ,I - One or more components in the glass can be used as a clarifier to improve the clarification effect of the glass and increase the bubble level of the glass. - Br - ,I - The content of each of these two compounds alone or in total is 0 to 2%, preferably 0 to 1%, and more preferably 0 to 0.5%.
[0072] <Ingredients not contained>
[0073] Components such as V, Cr, Mn, Fe, Co, Ni, Ag and Mo, even if contained in small amounts alone or in combination, will interfere with the spectral transmittance of the glass, which is not conducive to the formation of the near-infrared light absorbing glass of the present invention. Therefore, it is preferred not to contain the above components.
[0074] As, Pb, Th, Cd, Tl, Os, Be and Se components have been used as harmful chemical substances and have tended to be controlled in recent years. Environmental protection measures are necessary not only in the manufacturing process of glass, but also in the processing process and the disposal after productization. Therefore, in the case of paying attention to the impact on the environment, it is preferred that they are not actually contained except for the inevitable mixing. As a result, the glass does not actually contain substances that pollute the environment. Therefore, even if no special environmental countermeasures are taken, the glass of the present invention can be manufactured, processed and discarded.
[0075] The "does not contain" and "0%" recorded in this article mean that the component is not intentionally added as a raw material to the near-infrared light absorbing glass of the present invention; however, as raw materials and / or equipment for producing glass, there may be certain impurities or components that are not intentionally added, which may be contained in a small amount or trace amount in the final near-infrared light absorbing glass, and this situation is also within the scope of protection of the patent of this invention.
[0076] Next, the performance of the near-infrared light absorbing glass of the present invention will be described.
[0077] <Water resistance stability>
[0078] Water resistance stability of glass (D W ) (Powder method) Tested according to the method specified in the national standard "GB / T17129".
[0079] In some embodiments, the water resistance stability (D W ) is Class 1.
[0080] <Acid resistance stability>
[0081] Acid resistance of glass (D A ) (Powder method) Tested according to the method specified in the national standard "GB / T17129".
[0082] In some embodiments, the acid resistance stability (D A ) is 3 or more, preferably 2 or more.
[0083] <Transition Temperature>
[0084] The glass transition temperature (T g ) Tested according to the method specified in the national standard "GB / T7962.16-2010".
[0085] In some embodiments, the transition temperature (T g ) is 380 to 460°C, preferably 385 to 450°C, more preferably 390 to 440°C, and further preferably 395 to 430°C.
[0086] <density>
[0087] The density of glass (ρ) is tested according to the method specified in the national standard "GB / T7962.20-2010".
[0088] In some embodiments, the density (ρ) of the near-infrared light absorbing glass of the present invention is 3.5 g / cm 3 Below, preferably 3.4 g / cm 3 Below, more preferably 3.3 g / cm 3 Below, more preferably 3.2 g / cm 3 the following.
[0089] <Hardness>
[0090] The hardness of glass (H k ) Tested according to the method specified in the national standard "GB / T7962.18-2010".
[0091] In some embodiments, the hardness (H) of the near-infrared light absorbing glass of the present invention is k ) is 300kgf / mm 2 Above, preferably 310kgf / mm 2 More preferably 320kgf / mm 2 More preferably, 330 kgf / mm2 above.
[0092] <Young's modulus>
[0093] The Young's modulus (E) of glass is calculated using the following formula by ultrasonic testing of its longitudinal wave velocity and transverse wave velocity.
[0094]
[0095] Among them, in the formula:
[0096] E is Young's modulus, Pa;
[0097] G is the shear modulus, Pa;
[0098] V T is the shear wave velocity, m / s;
[0099] ρ is the glass density, g / cm 3 .
[0100] In some embodiments, the Young's modulus (E) of the glass of the present invention is 5500×10 7 ~7500×10 7 Pa, preferably 5700×10 7 ~7000×10 7 Pa, more preferably 5900×10 7 ~6900×10 7 Pa.
[0101] <Spectral transmittance>
[0102] The spectral transmittance of the glass of the present invention refers to the value obtained by a spectrophotometer in the above manner:
[0103] Assuming that the glass sample has two parallel and optically polished planes, light is vertically incident on one parallel plane and emerges from another parallel plane. The intensity of the emergent light divided by the intensity of the incident light is the transmittance, which is also called external transmittance.
[0104] When the glass thickness is less than 0.4 mm, the spectral transmittance has the characteristics described below:
[0105] In some embodiments, the spectral transmittance (τ 400 ) is 80.0% or more, preferably 82.0% or more, and more preferably 84.0% or more.
[0106] In some embodiments, the spectral transmittance (τ 500 ) is 83.0% or more, preferably 85.0% or more, and more preferably 88.0% or more.
[0107] In some embodiments, the spectral transmittance (τ 1100 ) is 20.0% or less, preferably 18.0% or less, more preferably 16.0% or less, and further preferably 14.0% or less.
[0108] In some embodiments, when the thickness of the near-infrared light absorbing glass is less than 0.4 mm, the wavelength (λ 50 ) is 640 nm or less, preferably 610 to 635 nm, and more preferably 615 to 630 nm.
[0109] The thickness of the glass sample is preferably 0.05 to 0.4 mm, more preferably 0.1 to 0.3 mm, further preferably 0.15 to 0.25 mm, and further preferably 0.15 mm, 0.18 mm, 0.20 mm, 0.21 mm, 0.23 mm, or 0.25 mm.
[0110] [Method for producing near-infrared light absorbing glass]
[0111] The manufacturing method of the near-infrared light absorbing glass of the present invention is as follows: the glass of the present invention is produced by conventional raw materials and conventional processes, using carbonates, nitrates, phosphates, metaphosphates, sulfates, hydroxides, oxides, fluorides, etc. as raw materials, and after the materials are prepared according to the conventional method, the prepared furnace materials are put into a melting furnace at 700-1000° C. for melting, and after clarification, stirring and homogenization, a homogeneous molten glass without bubbles and undissolved substances is obtained, and the molten glass is cast in a mold and annealed. Those skilled in the art can appropriately select raw materials, process methods and process parameters according to actual needs.
[0112] The near-infrared light absorbing glass of the present invention can also be formed by well-known methods. In some embodiments, the near-infrared light absorbing glass of the present invention can be manufactured into a formed body by various processes, and the formed body includes but is not limited to a sheet, and the process includes but is not limited to slit drawing, float process, rolling and other processes for forming sheets known in the art. Alternatively, the glass can be formed by a float process or rolling process known in the art. The near-infrared light absorbing glass of the present invention can be manufactured into a glass formed body of a sheet by methods such as grinding or polishing, but the method for manufacturing a glass formed body is not limited to these methods.
[0113] The near infrared light absorbing glass of the present invention can have any reasonably useful thickness.
[0114] [Near-infrared light absorbing glass element]
[0115] The near-infrared light absorbing glass element involved in the present invention contains the above-mentioned near-infrared light absorbing glass, and can be exemplified by a thin plate-shaped glass element or lens used in a near-infrared light absorbing filter, and is suitable for color correction of solid-state imaging elements, and has various excellent properties of the above-mentioned glass.
[0116] It should be noted that the thickness of the near-infrared light absorbing glass element (the distance between the incident surface and the exit surface of the transmitted light) is determined by the transmittance characteristics of the element. For convenience, the thickness is represented by a value of less than 0.4 mm in this article. It does not mean that it cannot be used for filter elements with other light absorption properties that can be obtained by changing the thickness.
[0117] [Filter]
[0118] The optical filter involved in the present invention is a near-infrared filter, which contains the above-mentioned near-infrared light absorbing glass or contains the above-mentioned near-infrared light absorbing glass element, and has a near-infrared light absorbing element composed of near-infrared light absorbing glass with both sides optically polished. This element gives the filter a color correction function and also has the various excellent properties of the above-mentioned glass.
[0119] [equipment]
[0120] The near-infrared light absorbing glass, or near-infrared light absorbing glass element, or filter of the present invention can be manufactured by well-known methods into devices such as portable communication devices (such as mobile phones), smart wearable devices, photographic devices, video equipment, display devices, and monitoring devices.
[0121] Example
[0122] <Near-infrared light absorbing glass example>
[0123] In order to further clearly illustrate and describe the technical solution of the present invention, the following non-limiting examples are provided.
[0124] This embodiment adopts the above-mentioned near-infrared light absorbing glass manufacturing method to obtain glass having the composition shown in Tables 1 to 3. In addition, the characteristics of each near-infrared light absorbing glass are measured by the testing method described in the present invention, and the measurement results are shown in Tables 1 to 3.
[0125] Table 1.
[0126]
[0127]
[0128] Table 2.
[0129]
[0130]
[0131] Table 3.
[0132]
[0133]
[0134] The near-infrared light absorbing glasses described in Tables 1 to 3 were processed into glass sheets with a thickness of 0.21 mm, and the spectral transmittance of the near-infrared light absorbing glasses of various embodiments was measured according to the test method described above. The results are shown in Tables 4 to 6 below.
[0135] Table 4.
[0136] Example 1# 2# 3# 4# 5# 6# 7# 8# <![CDATA[τ 400 (%)]]> 88.1 89.6 90.2 89.1 90.1 89.4 88.9 90.3 <![CDATA[τ 500 (%)]]> 89.2 90.3 90.7 90.1 91.3 90.7 89.6 91.5 <![CDATA[τ 1100 (%)]]> 4.8 4.8 4.8 5.3 5.4 5.3 5.2 5.2 <![CDATA[λ 50 (nm)]]> 613 618 619 619 620 618 616 618
[0137] Table 5.
[0138] Example 9# 10# 11# 12# 13# 14# 15# 16# <![CDATA[τ 400 (%)]]> 89.6 90.3 90.4 88.8 89.3 88.8 90.1 90.1 <![CDATA[τ 500 (%)]]> 90.6 91.0 91.6 90.4 90.7 90.2 90.9 90.4 <![CDATA[τ 1100 (%)]]> 6.0 5.7 7.9 7.4 6.9 6.9 5.5 8.7 <![CDATA[λ 50 (nm)]]> 623 623 625 626 625 622 621 630
[0139] Table 6.
[0140] Example 17# 18# 19# 20# 21# 22# 23# 24# <![CDATA[τ 400 (%)]]> 88.8 89.6 89.4 89.8 89.5 88.6 89.2 89.4 <![CDATA[τ 500 (%)]]> 89.6 90.8 90.6 91.0 90.7 89.4 90.2 90.4 <![CDATA[τ 1100 (%)]]> 1.4 7.2 7.2 13.5 12.8 0.9 6.8 7.1 <![CDATA[λ 50 (nm)]]> 606 626 625 639 637 603 624 625
[0141] <Near-infrared light absorbing glass element example>
[0142] The near-infrared light absorbing glasses of Examples 1 to 24# described above are made into near-infrared light absorbing glass elements by methods known in the art, and examples thereof include thin plate-shaped near-infrared light absorbing glass elements or lenses used in near-infrared light absorbing filters, which are suitable for color correction applications in solid-state imaging elements and possess various excellent properties of the above-mentioned glasses.
[0143] <Optical filter embodiment>
[0144] The near-infrared light absorbing glass and / or near-infrared light absorbing glass element of Examples 1 to 24# described above are made into optical filters by methods known in the art. The optical filters of the present invention have a color correction function and also possess various excellent properties of the above-mentioned glasses.
[0145] <Equipment Embodiment>
[0146] The near-infrared light absorbing glass and / or near-infrared light absorbing glass element and / or filter of the present invention can be manufactured by well-known methods into devices such as portable communication devices (such as mobile phones), smart wearable devices, photographic devices, video equipment, display devices, and monitoring devices. It can also be used in, for example, imaging devices, sensors, microscopes, medical technology, digital projection, optical communication technology / information transmission, or video equipment and devices in the vehicle field.
Claims
1. Near-infrared light absorbing glass, characterized in that: Its components are expressed in molar percentage, and the cationic component contains: P 5+ :38~52%;Al 3+ :3~12%;Cu 2+ :2~16%;Rn + :10~35%; R 2+ : 3-35%, said Rn + For Li + 、Na + , K + One or more of R 2+ Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ One or more of; The anion component contains: O 2- :82~97%;F - :3~18%.
2. The near-infrared light absorbing glass according to claim 1, characterized in that: Its components are expressed in molar percentage, and the cationic component also contains: Ln 3+ :0~8%;and / or B 3+ :0~5%;and / or Si 4+ :0~5%;and / or Zn 2+ :0~10%;and / or Sb 3+ : 0~3%, said Ln 3+ For La 3+ , Gd 3+ , Y 3+ One or more of; The anion component also contains: Cl - +Br - +I - :0~2%.
3. Near-infrared light absorbing glass, characterized in that: Its components are expressed in molar percentage, and the cationic component is represented by P 5+ :38~52%;Al 3+ :3~12%;Cu 2+ :2~16%;Rn + :10~35%; R 2+ :3~35%;Ln 3+ :0~8%; B 3+ :0~5%;Si 4+ :0~5%; Zn 2+ :0~10%; Sb 3+ : 0-3% composition, the Rn + For Li + 、Na + , K + One or more of R 2+ Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ One or more of Ln 3+ For La 3+ , Gd 3+ , Y 3+ One or more of; The anion component is O 2- :82~97%;F - :3~18%;Cl - +Br - +I - : 0~2% composition.
4. The near-infrared light absorbing glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in mole percentage, where: Rn + / (52%-P 5+ ) is 1.0 to 25.0, preferably Rn + / (52%-P 5+ ) is 1.4 to 20.0, and more preferably Rn + / (52%-P 5+ ) is 1.8 to 15.0, and more preferably Rn + / (52%-P 5+ ) is 2.2 to 10.0, and more preferably Rn + / (52%-P 5+ ) is 2.4 to 7.0, and the Rn + For Li + 、Na + , K + One or more of .
5. The near-infrared light absorbing glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in molar percentage, where: Al 3+ / Mg 2+ 1.0~10.0, preferably Al 3+ / Mg 2+ 1.1 to 8.0, more preferably Al 3+ / Mg 2+ 1.2 to 6.0, more preferably Al 3+ / Mg 2+ 1.3 to 4.0, more preferably Al 3+ / Mg 2+ It is 1.5 to 2.
5.
6. The near-infrared light absorbing glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in molar percentage, among which: Mg 2+ / Cu 2+ 0.1~1.8, preferably Mg 2+ / Cu 2+ 0.1 to 1.6, more preferably Mg 2+ / Cu 2+ 0.2 to 1.4, more preferably Mg 2+ / Cu 2+ 0.3 to 1.2, more preferably Mg 2+ / Cu 2+ It is 0.4~1.
0.
7. The near-infrared light absorbing glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in mole percentage, where: Rn + / Mg 2+ 2.0 to 30.0, preferably Rn + / Mg 2+ Rn is 2.5 to 24.0, and more preferably + / Mg 2+ is 3.0 to 18.0, and more preferably Rn + / Mg 2+ 3.5 to 12.0, and more preferably Rn + / Mg 2+ is 4.0 to 9.0, and the Rn + For Li + 、Na + , K + One or more of .
8. The near-infrared light absorbing glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in mole percentage, where: R 2+ / Mg 2+ 2.0~20.0, preferably R 2+ / Mg 2+ 2.2 to 15.0, more preferably R 2+ / Mg 2+ is 2.3 to 10.0, and more preferably R 2+ / Mg 2+ is 2.4 to 7.0, and more preferably R 2+ / Mg 2+ is 2.5 to 6.0, the R 2+ Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ One or more of .
9. The near-infrared light absorbing glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in molar percentage, among which: Ba 2+ / Cu 2+ 0.2 to 3.0, preferably Ba 2+ / Cu 2+ 0.3 to 2.5, more preferably Ba 2+ / Cu 2+ is 0.4 to 2.0, and Ba is more preferably 2+ / Cu 2+ is 0.5 to 1.5, and Ba is more preferably 2+ / Cu 2+ It is 0.5~1.
0.
10. The near-infrared light absorbing glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in molar percentage, among which: Zn 2+ / Cu 2+ 0 to 1.2, preferably Zn 2+ / Cu 2+ 0 to 1.1, more preferably Zn 2+ / Cu 2+ is 0 to 0.9, and Zn is more preferred 2+ / Cu 2+ 0 to 0.7, and more preferably Zn 2+ / Cu 2+ It is 0 to 0.
5.
11. The near-infrared light absorbing glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in molar percentage, where: F - / Mg 2+ 0.5~15.0, preferably F - / Mg 2+ 0.8 to 10.0, more preferably F - / Mg 2+ is 1.1 to 8.0, and more preferably F - / Mg 2+ is 1.3 to 6.0, and more preferably F - / Mg 2+ It is 1.5 to 4.
0.
12. The near-infrared light absorbing glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in molar percentage, where: (0.3×P 5+ +F - ) / Cu 2+ 1.5 to 9.0, preferably (0.3×P 5+ +F - ) / Cu 2+ 2.4 to 7.5, more preferably (0.3 × P 5+ +F - ) / Cu 2+ 3.3 to 6.0, more preferably (0.3×P 5+ +F - ) / Cu 2+ It is 3.5 to 5.
5.
13. The near-infrared light absorbing glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in molar percentage, where: P 5+ : 42~51%, preferably P 5+ : 44-50%; and / or Al 3+ : 4-10%, preferably Al 3+ : 5-8%; and / or Cu 2+ : 3-10%, preferably Cu 2+ : 4-8%; and / or Rn + : 15-30%, preferably Rn + : 20-28%; and / or R 2+ : 5-30%, preferably R 2+ : 10-20%; and / or Ln 3+ : 0~6%, preferably Ln 3+ : 0 to 4%, preferably no Ln 3+ ; and / or B 3 + : 0-2%, preferably B 3+ : 0 to 1%, preferably no B 3+ ; and / or Si 4+ : 0-2%, preferably Si 4+ : 0 to 1%, preferably no Si 4+ ; and / or Zn 2+ : 0-6%, preferably Zn 2+ : 0 to 4%, preferably no Zn 2+ ; and / or Sb 3+ : 0-2%, preferably Sb 3+ :0.01~1%, said Rn + For Li + 、Na + , K + One or more of R 2+ Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ One or more of Ln 3+ For La 3+ , Gd 3+ , Y 3+ One or more of .
14. The near-infrared light absorbing glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in molar percentage, where: Li + : 0-10%, preferably Li + : 0-7%, more preferably Li + :0~5%;and / or Na + : 10-32%, preferably Na + : 15-30%, more preferably Na + : 20-28%; and / or K+: 0-10%, preferably K + : 0-7%, more preferably K + :0~5%;and / or Mg 2+ : 1-10%, preferably Mg 2+ : 2-7%, more preferably Mg 2+ : 3-6%; and / or Ca 2+ : 1-10%, preferably Ca 2+ : 2-7%, more preferably Ca 2+ :3~6%;and / or Sr 2+ : 0-10%, preferably Sr 2+ : 1 to 8%, more preferably Sr 2+ : 2-6%; and / or Ba 2+ : 1-10%, preferably Ba 2+ : 2 to 8%, more preferably Ba 2+ : 3-6%; and / or Y 3+ : 0-6%, preferably Y 3+ : 0-5%, more preferably Y 3+ : 0-2%; and / or La 3+ : 0-5%, preferably La 3+ : 0-3%, more preferably La 3+ :0~1%;and / or Gd 3+ : 0-5%, preferably Gd 3+ : 0-3%, more preferably Gd 3+ :0~1%.
15. The near-infrared light absorbing glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in mole percentages, where: O 2- : 85 to 95%, preferably: O 2- : 87 to 93%; and / or F - : 5 to 15%, preferably F - : 7 to 13%; and / or Cl - +Br - +I - : 0 to 1%, preferably Cl - +Br - +I - : 0 to 0.5%.
16. The near-infrared light absorbing glass according to any one of claims 1 to 3, characterized in that: The water resistance stability of the near-infrared light absorbing glass is D W Class 1; and / or acid resistance stability D A 3 or more, preferably 2 or more; and / or transition temperature T g 380 to 460°C, preferably 385 to 450°C, more preferably 390 to 440°C, and further preferably 395 to 430°C; and / or density ρ is 3.5 g / cm 3 Below, preferably 3.4 g / cm 3 Below, more preferably 3.3 g / cm 3 Below, more preferably 3.2 g / cm 3 Below; and / or hardness H k 300kgf / mm 2 Above, preferably 310kgf / mm 2 More preferably 320kgf / mm 2 More preferably, 330 kgf / mm 2 and / or Young's modulus E is 5500×10 7 ~7500×10 7 Pa, preferably 5700×10 7 ~7000×10 7 Pa, more preferably 5900×10 7 ~6900×10 7 Pa.
17. The near-infrared light absorbing glass according to any one of claims 1 to 3, characterized in that: Near infrared light absorbing glass with a thickness of less than 0.4mm, spectral transmittance τ at 400nm wavelength 400 80.0% or more, preferably 82.0% or more, more preferably 84.0% or more; and / or the spectral transmittance τ at a wavelength of 500 nm 500 83.0% or more, preferably 85.0% or more, more preferably 88.0% or more; and / or the spectral transmittance τ at a wavelength of 1100 nm 1100 20.0% or less, preferably 18.0% or less, more preferably 16.0% or less, and further preferably 14.0% or less; and / or the wavelength λ corresponding to the transmittance of 50% in the spectral transmittance within the wavelength range of 500 to 700 nm is 50 The wavelength is 640 nm or less, preferably 610 to 635 nm, and more preferably 615 to 630 nm.
18. The near-infrared light absorbing glass according to claim 17, characterized in that: The thickness of the near-infrared light absorbing glass is 0.05 to 0.4 mm, preferably 0.1 to 0.3 mm, more preferably 0.15 to 0.25 mm, and further preferably 0.15 mm, 0.18 mm, 0.20 mm, 0.21 mm, 0.23 mm, or 0.25 mm.
19. A near-infrared light absorbing glass element, characterized in that: It is made of the near-infrared light absorbing glass described in any one of claims 1 to 18.
20. An optical filter, characterized in that A device comprising the near-infrared light absorbing glass according to any one of claims 1 to 18, or comprising the near-infrared light absorbing glass element according to claim 19.
21. A device, characterized in that A near-infrared light absorbing glass according to any one of claims 1 to 18, or a near-infrared light absorbing glass element according to claim 19, or an optical filter according to claim 20.
Citation Information
Patent Citations
Near-infrared light absorbing glass, element and light filter
CN104341105A